Consistent dust electrification from Arabian Gulf sea breezes. (12th August 2020) - Nicoll, Keri; Harrison, Giles; Marlton, Graeme; Airey, Martin
Abstract: The Arabian Gulf region experiences regular thermally driven sea breeze circulations which occur all year round, penetrating hundreds of kilometres inland. As a sea breeze front moves inland, substantial electric fields are generated by separation of charged desert dust. In the first surface electric field measurements made in the United Arab Emirates (UAE), consistent and repeatable substantial electric field changes with magnitudes up to 7 kV m −1 have been detected at Al Ain (170 km from the western coast), during 80 separate sea breeze events in 2018. Every sea breeze frontal passage shows the same characteristic signature of a transient maximum peak in electric field lasting tens of minutes. Electric field changes during these events were always negative (i.e. enhancing the existing negative 'fair weather' electric field), in contrast to many other reported observations in dust storms in which conditions were less repeatable. The regular and substantial dust electrification found demonstrates that accurate representation of dust in climate and weather models requires electrical effects to be addressed, both in the generation process, and by considering aggregates in radiative transfer calculations as electrically aligned rather than randomly ordered. Furthermore, satellite aerosol retrievals are affected by the changed attenuation of electromagnetic radiation when dust particles are charged, for which corrections may be needed.